RANCANG BANGUN APLIKASI PENGGALANGAN DANA MENGGUNAKAN ALGORITMA REVERSE COLUSSI BERBASIS WEB - Riki Yuspika; aah sumiah; tito sugiharto (FKOM UNIKU, 2017)
Along with the development era of ease in doing an activity is increasing, such as in fund raising for natural disasters that occur around the environment even in other environments. The fundraising process is commonly done conventionally or by way of direct descent into the street. The conventional fundraising process has a deficiency in terms of effectiveness because of the large number of members who have to go down the road and the lack of transparency of incoming funds due to no publication of reports, not yet computerized reports of fundraising results. Therefore it is necessary for a media that can assist in the process of fundraising to facilitate the conduct of fundraising. Website creation by implementing Algorithm can improve the function of the website, Revese Colussi Algorithm as String Matching Algorithm can be implemented in a search in website so that search can be more effective. Research methodology of software development used in this research is RUP (Rational Unified Process). In this peneliltian writer using PHP programming language with Dream Weaver as its editor, besides writer use PHP MySQL as database. And for the testing process using Black Box Testing and White Box Testing.Keywords: Fundraising, String Matching Algorithm, Reverse Colussi Algorithm, Rational Unified Process, PHP, PHP MySQL, Black Box Testing, White Box Testing